2006
DOI: 10.1200/jco.2006.24.18_suppl.18580
|View full text |Cite
|
Sign up to set email alerts
|

Loading dose ibandronate in rapid pain management of metastatic bone disease (MBD)

Abstract: 18580 Background: MBD is common complication in many malignancies. Pain is common presentation of MBD. It is major cause of morbidity, major determinant of quality of life and an important reason for emergency medical referral. Acute pain necessitates emergency pain relief measures. Besides conventional radiation and pain killers, bisphosphonates are indicated in MBD. They contribute towards pain relief. Literature suggests that ibandronate may be effective in acute pain relief. The aim of this study was to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Recently, 2 pilot studies found that loading-dose ibandronate 6 mg for 3 consecutive days can reduce bone pain within approximately 2-7 days of infusion, regardless of tumor type. 45,46,53 However, because pain is a symptom of the underlying pathophysiology, pain outcomes and bone health are important to consider, and these studies have not assessed whether this dosing schedule reduced SREs.…”
Section: Results Trialmentioning
confidence: 99%
“…Recently, 2 pilot studies found that loading-dose ibandronate 6 mg for 3 consecutive days can reduce bone pain within approximately 2-7 days of infusion, regardless of tumor type. 45,46,53 However, because pain is a symptom of the underlying pathophysiology, pain outcomes and bone health are important to consider, and these studies have not assessed whether this dosing schedule reduced SREs.…”
Section: Results Trialmentioning
confidence: 99%
“…The recommended dose and schedule of bisphosphonate therapy have been established in registration trials, although alternate treatment schedules for bisphosphonate therapy are under investigation. Several nonstandard, intensive treatment regimens of intravenous ibandronate have been evaluated in patients with metastatic bone disease for acute bone pain relief, followed by the approved monthly infusions [97][98][99]. Results from these pilot studies suggest that alternate ibandronate schedule provided acute pain relief, and that more flexible or individualized bisphosphonate treatment may provide clinical benefits.…”
Section: Discussionmentioning
confidence: 99%